Locus of attachment: peran identitas lokal terhadap work engagement dan turnover intention di wilayah kepulauan - Putri Amalia; Putri Abdul Aziz; Ilda Italia Jabib; Rahmat Sabuhari; Muhammad Asril Arilaha (MAMEN: Jurnal Manajemen, 2026)
High employee turnover rates in island regions like Ternate have become a strategic issue that can trigger brain drain and hinder regional development. This study aims to empirically examine the influence of work engagement and local identity on employee turnover rates among professionals in Ternate. The study involved 185 respondents selected using a purposive sampling technique. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that the model explained 55.5% of the variance in employee turnover rates (R² = 0.555). Partially, local identity had a significant effect on employee turnover rates (P = 0.000), while work engagement showed no significant effect (P = 0.127). The results indicate that sociocultural attachment and regional identity are more dominant factors in shaping employee loyalty than individual psychological factors alone. Therefore, organizations operating in island regions should emphasize local wisdom and regional identity as part of their employee retention strategies to reduce employee turnover intentions and strengthen workforce stability.